Prozac on the couch prescribing gender in the era of wonder drugs - Metzl, Jonathan Michel 1964- (Duke University Press, 2012)
1. Introduction: The Freud of Prozac -- 2. The Name of the Father, the Place of the Medication: A Brief History of Psychiatry, 1955-2002 -- 3. Anxiety, the Crisis of Psychoanalysis, and the Miltown Resolution, 1955-60 -- 4. The Gendered Psychodynamics of Pharmaceutical Advertising, 1964-97 -- 5. Prozac and the Pharmacokinetics of Narrative Form, 1994-2002 -- 6. Conclusion
Informationen wurden der Landingpage entnommen, da weder Titelblatt noch Impressum vorhanden sind (Duke University Press)
Keywords: Geschichte 1950-2003; Neuropsychiatry; Psychopharmacology; Psychoanalysis; Gender identity; Medicine / Mental health; Psychoanalyse; Psychopharmakotherapie; Geschlechterrolle; Kulturelles System